Analytical Study of Similarity and Contrast Of Arabic Sounds in Indonesian Language (ar) - Sirdiono Nata Akbar; Muflihah Muflihah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2019)
It is unthinkable that errors in the pronunciation of Arabic voices can hinder understanding and lead to ambiguity and ambiguity in meaning. This study aims to determine the sound errors that researchers witnessed in Luqman al-Hakim Surabya school students. This study uses descriptive and qualitative methods for field research. The source of the data consists of primary data (samples of class II A students) and secondary data found from references related to research. While the method for collecting research data is using observation and interviews. After conducting research at the Luqman Al-Hakim School in Surabaya, the researcher found a sound error, namely the mention of letters that are similar to Tatwiriyah errors and errors in the mention of sounds in Arabic that are not found in Indonesian, namely the Prayer of Blessing. the cause of errors in the mention of the sound of Arabic in class II A students at Luqman Al-Hakim Surabaya School is ignorance and lack of application of rules in terms of sound also because of the influence of mother tongue, namely Indonesian.It is unthinkable that errors in the pronunciation of Arabic voices can hinder understanding and lead to ambiguity and ambiguity in meaning. This study aims to determine the sound errors that researchers witnessed in Luqman al-Hakim Surabya school students. This study uses descriptive and qualitative methods for field research. The source of the data consists of primary data (samples of class II A students) and secondary data found from references related to research. While the method for collecting research data is using observation and interviews. After conducting research at the Luqman Al-Hakim School in Surabaya, the researcher found a sound error, namely the mention of letters that are similar to Tatwiriyah errors and errors in the mention of sounds in Arabic that are not found in Indonesian, namely the Prayer of Blessing. the cause of errors in the mention of the sound of Arabic in class II A students at Luqman Al-Hakim Surabaya School is ignorance and lack of application of rules in terms of sound also because of the influence of mother tongue, namely Indonesian.